Tracing the Conflict Between Türkiye and Syria Through the Turkish Mainstream Media's Coverage of the Syrian President Bashar al‐Assad - ŞENYÜZ, FATMA BİLGE (My University, 2024)
The Syrian civil war began in March 2011 and spread throughout the country in April 2011. There-fore, in this study news articles and columns published in 2011 were selected and analyzed through pur-posive sampling. This study uses content analysis to examine the coverage of Syrian President Basharal-Assad in mainstream print newspapers with different ideological orientations in T€urkiye. The theoreti-cal framework of this study is based on the concept of localization of foreign news. The research has thepotential to reveal both the transformation of the tone of media texts over time and the similarities anddifferences in the coverage of an international conﬂict by newspapers with different ideological orienta-tions. Despite ideological differences, the study reveals similarities in the orientation of the newspapersstudied toward local interests. The dominance of Turkish ofﬁcials as news actors, the limited portrayal ofSyrian security forces, and the selection of photographs reinforce the parallel stance with Turkish foreignpolicy. The media’s tone toward Assad and Syrian politics became more negative and critical as the con-ﬂict escalated.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (Soc); Social Sciences (Soc)